Strategies to Build Pentahelix Partnerships in the Development of Mangrove Ecotourism as a Tourist Destination in Batam City - Silitonga, Frangky; Kartika Cahayani; Tirta Mulyadi; Rosie Oktavia Puspita Rini; Okta Safitri; Yobel Ketaren (JURNAL KEKER WISATA, 2025)
Kampung Tua Bakau Serip Tourism Village is starting from the concern about the change in the function of the mangrove forest and the potential in it such as the center for selling handicrafts, culinary, halfway houses and tourist destinations which have been a strong support for the community's economy in Kampung Tua Bakau Serip. Therefore, it is necessary to create synergy between various stakeholders in supporting the development of sustainable tourism in Kampung Tua Bakau Serip village. The Pentahelix model integrates five main elements, namely the government, society, academics, businesspeople, and the media, each of which has an important role in strengthening local tourism potential and maximizing community resources in Kampung Tua Bakau Serip. Through this PKM, it will be able to optimize the existence of mangrove forests and local culture, increase the economic empowerment of local communities through fishermen's catches and handicrafts. Through the involvement of the business sector, such as companies or MSME actors, the development of village economic potential can be more directed and sustainable, the fishermen's catch in the form of clams or barkgongs can be managed into culinary specialties and clam shells and barks can be managed into handicrafts in the form of frames, key toys, bags, and wall decorations. This collaboration can help overcome challenges such as budget constraints, training needs for residents of Kampung Tua Bakau Serip, and become an example of a tourist village in Indonesia. From the description above, innovation is needed with the creation of the Pentahelix collaboration model in Kampung Tua Bakau Serip Tourism Village so that concerns about changes in forest function and the potential that has existed so far such as the development of handicraft sales centers, culinary, halfway houses, and mangrove touring tourist destinations which have been a strong support for the community's economy in Kampung Tua Bakau Serip will continue to develop as an attractive tourist destination. sustainable, and have a positive impact on the local community as well as examples of tourist villages in Indonesia.